The effects of block‐based visual and text‐based programming training on students' achievement, logical thinking skills, and motivation - Saygıner, Şenol; Tüzün, Hakan (Journal of computer assisted learning, 2023)
Background Studies on the effectiveness of block‐based environments continue to produce inconsistent results. A strong reason for this is that most studies compare environments that are not equivalent to each other or to the level of learners. Moreover, studies that present evidence of the effectiveness of block‐based environments by comparing equivalent environments are limited. Objectives This study aims to scrutinize the effects of programming training to be held in equivalent environments (block‐based and text‐based) with university students who do not have prior programming knowledge and experience on achievement, logical thinking, and motivation. Methods The study was conducted by using an experimental pretest‐posttest control group design. The study was conducted with 60 students, the total consisting of 30 students in the experimental group and 30 students in the control group. In the experimental group, block‐based visual programming training with Scratch was conducted and the control group received text‐based programming training with Small Basic. The training was maintained for 10 weeks, for 4 h a week in each group. The programming achievement test, the logical thinking skills test, and the motivation scale were used to collect the data. Results and Conclusions The results showed that the use of a block‐based environment in programming training contributed positively to the development of students' logical thinking skills, and motivation for learning programming. In contrast, there was evidence that this training did not make a difference on programming success. Implications The findings of the study provided evidence of the effectiveness of block‐based training in comparisons made in equivalent environments. Focusing research on this issue may contribute to the improvement of the current understanding. Lay Description What is already known about this topic? Programming is a competency that students have difficulty in the learning process. Studies on the effectiveness of block‐based environments present inconsistent results. Studies examining the effectiveness of learning programming in equivalent environments (such as Scratch versus Small Basic) are limited. What this paper adds? The effectiveness of programming environments was examined in equivalent environments. Learning programming in a block‐based environment contributed more positively to students' logical thinking and motivation. The impact of block and text‐based environments on programming achievement was similar. Implications for practice and/or policy The use of a block‐based environment in programming education provides positive contributions to the development of novice undergraduate students' logical thinking skills and motivation. The issue of equivalence of environments is critical in research comparing programming achievement.